Enhanced heterogeneous Fenton degradation of Methylene Blue by nanoscale zero valent iron (nZVI) assembled on magnetic Fe3O4/reduced graphene oxide. (April 2015) - Yang, Bo; Tian, Zhang; Zhang, Li; Guo, Yaopeng; Yan, Shiqiang
Abstract: Highly effective nanoscale zero valent iron (nZVI) immobilized on magnetic Fe3 O4 -reduced graphene oxide (Fe 0 –Fe3 O4 –RGO) was successfully fabricated and firstly proposed as a heterogeneous Fenton catalyst for the removal of Methylene Blue (MB). The characterization of the hybrids revealed that Fe3 O4 were distributed on RGO nanosheets evenly, the nZVI were wrapped by Fe3 O4 assembled on the RGO nanosheets. The effects of pH value, initial concentration of MB, catalyst dosage, and hydrogen peroxide (H2 O2 ) concentration on the degradation of MB were systematically investigated. Typically, 98.0% removal of 50 mg/L MB could be achieved within 60 min with the initial pH value of 3.00, H2 O2 concentration 0.8 mmol/L, catalyst dose 0.10 g/L. The analysis of kinetics showed that the removal of MB followed the pseudo-second-order kinetics better than the pseudo-first-order kinetics. In addition to its high catalytic activity, the reusability and superparamagnetism make it a promising candidate as heterogeneous Fenton catalyst to remove organic contaminants in water.